Tahfidz Al-Qur'an Learning Model at Hidayatullah Putri Islamic Boarding School, Ohoitel Village, North Dullah District, Tual City, Maluku Towards a World-Class Campus - Maulana Ishaq Ernas (Budapest International Research and Critics University, 2022)
The learning model is a conceptual framework that describes and describes a systematic procedure in organizing learning and learning experiences to achieve learning objectives and serves as a guide in learning planning for educators in carrying out learning activities. The tahfidz Al - Qur'an learning model is a conceptual design that is systematically compiled as a guide for teachers to achieve certain goals in memorizing the Qur'an. Learning tahfiz Al-Qur'an can also be defined as the process of memorizing the Qur'an in memory so that it can be pronounced or uttered out of the head correctly in certain ways continuously. The tahfidz Al-Qur'an learning program at the Hidayatullah Putri Ohoitel Islamic Boarding School has two programs, namely by using a regular or regular program which is a learning program that targets students to be able to make mandatory deposits within a week of at least two sheets of Al-Qur'an attachments. . As for the second program, namely the special Al-Qur'an tahfidz program where female students at the Hidayatullah Ohoitel Islamic Boarding School use a 6-month memorization program which is a learning program to target students who can and can memorize the Qur'an within 6 months by doing mandatory deposit a day at least 2 sheets of attachments to the Qur'an. In the process of learning tahfidz Al-Qur'an Islamic Boarding School Hidayatullah Putri Ohoitel uses a combined method or more than one method used by female students in memorizing the Qur'an. The tahfidz Al-Qur'an learning model at the Hidayatullah Putri Ohoitel Islamic Boarding School uses a learning model centered on female students with the type of personal learning model.